Effect of living donor liver transplantation on depressive symptoms in hepatitis C virus patients. Issue 1 (January 2016) - Hashem, Reem E.L.S.; Sabry, Walaa; ELSaid, Tamer W.; Montasser, Iman F.; El Gendy, Eman; William, Peter
Abstract : Background: The number of liver transplantations has shown a steady increase over time, with increasing emphasis on psychosocial assessment. The goal of liver transplantation is not only to promote patient survival but also to enhance their quality of life and mental well-being. Pretransplant psychiatric evaluation is used to identify psychiatric illnesses and psychological problems in transplant candidates in order to improve patient outcome. This study aimed at exploring the impact of living donor liver transplantation on depressive symptoms reported by hepatitis C virus (HCV) recipients during their preoperative psychological assessment. Materials and methods: Thirty-five recipients with HCV-related liver cirrhosis who had undergone living donor liver transplantation were prospectively assessed using a self-rating scale – the Beck Depression Inventory – for the evaluation of depressive symptoms. The evaluation was carried out three times: before transplantation, 1 month after transplantation, and 6 months after transplantation. Results: The preoperative depression scores were found to be significantly higher with a mean of 21.80±3.36 as compared with the postoperative scores at 1 (11.74±2.24) and 6 months (7.6±2.43) ( P <0.0005). In addition, no statistically significant differences were found on comparing the baseline Beck Depression Inventory scores of patients with hepatocellular carcinoma along with HCV versus those with only HCV disease, nor for Child class B versus class C patients. Conclusion: Self-reported depression scores for recipients with HCV-related liver diseases showed a greater improvement after living donor liver transplantation surgery. Hence, transplantation has a favorable outcome on the psychological burden experienced by transplant recipients, thereby contributing toward their well-being.